Microscopic Detection of L.D. Bodies in Splenic Aspirates at Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2009)
Leishman stained smears prepared from ninety-nine (99) splenic aspirates and eleven (11) slitskin were examined under light microscope in order to detect L.D. bodies at the department ofMicrobiology, Rajshahi Medical College from 2002 to May 2003. L.D. bodies were found in 46(46.46%) and 01 (9.09%) samples of splenic aspirates and slit skin smears respectively. Smearpositivity and concomitant higher parasitic load was noted among comparatively younger agegroups with slight male preponderance. Demonstration of parasitic by direct microscopicalexamination in splenic aspirates for the diagnosis of visceral leishmaniasis or kala azar and inslit skin smears for Post kala azar dermal leishmaniasis (PKDL) is reliable method.doi: 10.3329/taj.v16i1.3898TAJ June 2003; Vol.16(1): 20-23